2018
DOI: 10.1186/s12951-018-0372-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunoassays for scarce tumour-antigens in exosomes: detection of the human NKG2D-Ligand, MICA, in tetraspanin-containing nanovesicles from melanoma

Abstract: BackgroundTumour-derived exosomes can be released to serum and provide information on the features of the malignancy, however, in order to perform systematic studies in biological samples, faster diagnostic techniques are needed, especially for detection of low abundance proteins. Most human cancer cells are positive for at least one ligand for the activating immune receptor NKG2D and the presence in plasma of NKG2D-ligands can be associated with prognosis.MethodsUsing MICA as example of a tumour-derived antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Further, our data suggest that sMICA in plasma of MICAgen mice is, at least in part, derived from hematopoietic cells that up-regulated and shed MICA upon activation ( Figure 5). Such sMICA may differ in its effects on NKG2D modulation from tumor-released MICA, especially when embedded in exosomes (45,48,49). Of note, activation-induced surface MICA is vanishing over several days past activation, and it will be interesting to determine the mechanisms not only underlying MICA induction but also underlying the reversal of MICA surface expression.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our data suggest that sMICA in plasma of MICAgen mice is, at least in part, derived from hematopoietic cells that up-regulated and shed MICA upon activation ( Figure 5). Such sMICA may differ in its effects on NKG2D modulation from tumor-released MICA, especially when embedded in exosomes (45,48,49). Of note, activation-induced surface MICA is vanishing over several days past activation, and it will be interesting to determine the mechanisms not only underlying MICA induction but also underlying the reversal of MICA surface expression.…”
Section: Discussionmentioning
confidence: 99%
“…TDE expressing NKG2D ligands are a means that tumor cells use for immune-evasion [ 74 ]. It has been demonstrated that ovarian cancer and melanoma TDEs, express NKG2D ligands and prevent activation of cytotoxic NK cells [ 75 , 76 ]. Expression of FASL and TRAIL on TDEs induce apoptosis in dendritic cells (DCs) and peripheral blood mononuclear cells (PBMCs) which causes immunosuppression and promotes tumor progression [ 77 ].…”
Section: Evs and Cancer Immunotherapymentioning
confidence: 99%
“…The feasibility of exosome uptake by recipient cells, make these cell products for introducing in clinical approaches. Xue and colleagues investigated the effects of cord blood and adipose-derived MSC exosomes on human EC angiogenesis capacity under hypoxic and normal conditions [106,107]. They noted the potency of isolated exosomes in triggering angiogenesis rate especially under the hypoxic condition compared to exosome counterpart originated from normal milieu.…”
Section: Exosomal Pro-and Anti-angiogenic Factorsmentioning
confidence: 99%